2005
DOI: 10.1016/j.chembiol.2004.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Wortmannin, a Widely Used Phosphoinositide 3-Kinase Inhibitor, also Potently Inhibits Mammalian Polo-like Kinase

Abstract: Polo-like kinases (PLKs) play critical roles throughout mitosis. Here, we report that wortmannin, which was previously thought to be a highly selective inhibitor of phosphoinositide (PI) 3-kinases, is a potent inhibitor of mammalian PLK1. Observation of the wortmannin-PLK1 interaction was enabled by a tetramethylrhodamine-wortmannin conjugate (AX7503) that permits rapid detection of PLK1 activity and expression in complex proteomes. Importantly, we show that wortmannin inhibits PLK1 activity in an in vitro kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
149
1
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(158 citation statements)
references
References 51 publications
5
149
1
3
Order By: Relevance
“…The active site lysine (Lys802 in p110α and Lys833 in p110γ) is critical for catalysis and is highly conserved in lipid and protein kinases. Wortmannin also targets class II PI3K C2β (IC 50 =1.6 nM), the human class III PI3K hVps34p (IC 50 = 2.5 nM), type III PI4Ks (IC 50 =50-300 nM) and polo-like protein kinases that regulate mitosis (IC 50 =24-48 nM) [60][61][62][63][64]. Not surprisingly, considering the similarity between the PI3K and PIKK catalytic domains, wortmannin also irreversibly inhibits PIKK family members.…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%
“…The active site lysine (Lys802 in p110α and Lys833 in p110γ) is critical for catalysis and is highly conserved in lipid and protein kinases. Wortmannin also targets class II PI3K C2β (IC 50 =1.6 nM), the human class III PI3K hVps34p (IC 50 = 2.5 nM), type III PI4Ks (IC 50 =50-300 nM) and polo-like protein kinases that regulate mitosis (IC 50 =24-48 nM) [60][61][62][63][64]. Not surprisingly, considering the similarity between the PI3K and PIKK catalytic domains, wortmannin also irreversibly inhibits PIKK family members.…”
Section: Mtor Kinase Inhibitorsmentioning
confidence: 99%
“…In Vitro Kinase Reaction-To identify the possible Thr residue(s) of p73␣ that could be phosphorylated by Plk1, we used CycLex Polo-like kinase 1 assay kit (CycLex, Nagano, Japan) (29). In brief, the purified Plk1 was added to the reaction mixture containing 50 M ATP and polyclonal anti-phospho-Thr antibody and incubated for 30 min at room temperature.…”
Section: Construction Of Mutant Forms Of Gst-p73␣-(1-130)-mentioning
confidence: 99%
“…Results from these experiments revealed that only the activities of the β1/β1i and β5/β5i subunits of the proteasome were inhibited by bortezomib [37,38]. The cancer drug, paclitaxel, used to treat breast and ovarian cancers, has also been tested for its efficacy in a cell-based assay using a wortmannin-containing ABP that targets polo-like kinase 1 (PLK1), an enzyme with highly elevated activity in the M phase of the cell cycle [39]. Since paclitaxel arrests the cell cycle at M phase, the elevated activity levels of PLK1 in Jurkat cells treated with this drug were monitored using the wortmannin-containing ABP [39].…”
Section: Enzyme Inhibitor Discovery and Verificationmentioning
confidence: 99%
“…The cancer drug, paclitaxel, used to treat breast and ovarian cancers, has also been tested for its efficacy in a cell-based assay using a wortmannin-containing ABP that targets polo-like kinase 1 (PLK1), an enzyme with highly elevated activity in the M phase of the cell cycle [39]. Since paclitaxel arrests the cell cycle at M phase, the elevated activity levels of PLK1 in Jurkat cells treated with this drug were monitored using the wortmannin-containing ABP [39]. This study demonstrated that PLK1 activity could potentially serve as a biomarker for paclitaxel efficacy in cancer treatment.…”
Section: Enzyme Inhibitor Discovery and Verificationmentioning
confidence: 99%